ORGANIZATION OF THE FIRST-LINE LIFE SUPPORT OF THE AFFECTED POPULATION IN AREAS WHERE EMERGENCY SITUATIONS OCCUR (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines the organization and implementation of first-line life support for the affected population in emergency situations. It emphasizes the importance of timely and coordinated efforts in providing critical medical assistance, ensuring public safety, and restoring basic services in disaster-stricken areas. The study also evaluates different methods and strategies used in the field, highlighting their effectiveness and challenges. Practical recommendations for improving first-response systems are provided to better address emergencies in the future.